National institutional plan for adaptation to climate change for agricultural sector in Honduras (2019-2023) - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
This national plan, issued by the secretariat of agriculture (SAG) set the priority action for adaptation to climate change in Honduras, integrating gender and sustainable climate food system strategic axes.